Temporomandibular joint involvement in childhood arthritis: comparison of ultrasonography-assessed capsular width and MRI-assessed synovitis - Kirkhus, Eva (Dentomaxillofac Radiol, 2016)
OBJECTIVES: Ultrasonography is an effective, low-cost, low-threshold and convenient diagnostic tool in childhood arthritis, but its value in temporomandibular joint (TMJ) involvement is not clear. The purpose of our study was to explore the reliability of ultrasonography to assess TMJ inflammation using contrast-enhanced MRI as reference standard, in order to deduce cut-off values for TMJ capsular width to detect enhanced synovial thickening (synovitis). METHODS: 124 ultrasonography and MRI examinations in 55 patients [mean age 12.4 ± 3.5 years (±standard deviation)], the majority obtained within 1 day, were scored for subcondylar and condylar capsular width (ultrasonography images) and amount of synovitis (MR images). The correlations of these findings were calculated. A receiver operating characteristic (ROC) curve analysis, with MRI findings as reference standard, was obtained. RESULTS: The correlation between ultrasonography-assessed capsular width and MRI-assessed amount of synovitis was moderate both at the subcondylar and condylar level [Spearman's rho (ρ): 0.483; p < 0.001 and 0.347; p < 0.001 respectively]. The ROC curve indicated the best discriminatory ability at the subcondylar level with an area under the curve of 0.77 (95% confidence interval 0.69–0.85) and a cut-off value of 1.2 mm (sensitivity 72%, specificity 70%) for the capsular width. CONCLUSIONS: A moderate correlation between ultrasonography-assessed capsular width and MRI-assessed synovitis was found in childhood arthritis with the best discriminatory ability at the subcondylar level. This indicates that ultrasonography may be a valuable diagnostic tool in the initial assessment of TMJ inflammation.